ESTUDO DE PROPRIEDADES DO CRISTAL TRIS(1,10-FENANTROLINA)FERRO(III) TRINITRATO MONOHIDRATADO - REIS , Ian Felipe Sousa (2020)
Metal complexes based on N,N'-heterocyclic chelators have been explored due to the possibility of combining the thermodynamic and kinetic properties of metals and chelators. Thus, this work aims to synthesize the crystals from 1,10-phenanthroline and iron (III) nitrate, to study their structural, vibrational and thermal properties for application as an anti-tumor. The crystals were synthesized at room temperature, using the slow solvent evaporation technique using a supersaturated solution with equimolar proportion of the starting compounds. Soon after obtaining the tris (1,10-phenanthroline)iron(III) trinitrate monohydrate crystal it was characterized by X-ray diffraction (XRD) at room temperature together with the Rietveld method, Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, theoretical calculation based on the density functional theory (DFT), thermogravimetric analysis (TG), differential thermal analysis (DTA), XRD as a function of temperature and Raman as a function of temperature. Through XRD in conjunction with the Rietveld method, it was found that the crystal crystallizes in a monoclinic structure and with C2 / C spatial group, with four molecules per unit cell and lattice parameters a = 10.758 (8) Å, b = 24,550 (13) Å, c = 13,259 (5) Å and β = 103,022º. Structural parameters of lengths and connection angles were obtained by DFT and compared with those of XRD, showing satisfactory results. The FTIR and Raman spectra showed good agreement with those obtained through DFT and, therefore, comproved the complexation of metal to Fen, due to the appearance of bands referring to the NO3⁻ and Fe3+ groups in the spectrum, as well as the shift of the heterocyclic ring groups of the Fen. Through thermal analysis, it was observed that the crystal loses crystallization water between 315-362 K, followed by the exit of the nitrate molecule between 363-437 K and decomposition after 438 K. Analyzing the lattice parameters of the crystal through the XRD as a function of temperature, it was possible to observe that there was a conformational phase transformation from 323 K, due to the transition to the anhydrous structure. From the studies by Raman spectroscopy as a function of temperature, the morphological transition pointed out by the XRD as a function of temperature was validated and justified by the attempt to adapt the molecules to the new anhydrous conformation. The techniques employed showed that the material presented low thermal stability around 315 K and structural variability.